LO24: Is prehospital care supported by evidence-based guidelines? An environmental scan and quality appraisal using AGREE II. (15th May 2017) - Turner, S.; Lang, E.; Brown, K.; Leyton, C.; Bulger, E.; Sayre, M.; Kraus, D.; Lee Robertson, H.
Abstract : Introduction: The Institute of Medicine (IOM) has recommended that high-quality, evidence-based guidelines be developed for emergency medical services (EMS). The National Association of EMS Physicians (NAEMSP) has outlined a strategy that will see this task fulfilled, consisting of multiple working groups focused on all aspects of guideline development and implementation. A first step, and our objective, was a cataloguing and appraisal of the current guidelines targeting EMS providers.Methods: A systematic search of the literature was conducted in MEDLINE (1175), EMBASE (519), PubMed (14), Trip (416), and guidelines.gov (64) through May 1, 2016. Two independent reviewers screened titles for relevance to prehospital care, and then abstracts for essential guideline features, including a systematic review, a grading system, and an association between level of evidence and strength of recommendation. All disagreements were moderated by a third party. Citations meeting inclusion criteria were appraised with the AGREE II tool, which looks at six different domains of guideline quality, containing a total of 23 items rated from 1 to 7. Each guideline was appraised by three separate reviewers, and composite scores were calculated by averaging the scaled domain totals.Results: After primary (kappa 97%) and secondary (kappa 93%) screening, 49 guidelines were retained for full review. Only three guidelines obtained a score of >90%, the topics of which included aeromedical transport, analgesia in trauma, and resuscitation of avalanche victims. Only two guidelines scored between 80% and 90%, the topics of which included stroke and pediatric seizure management. One guideline, splinting in an austere environment, scored between 70% and 80%. Nine guidelines scored between 60% and 70%, the topics of which included ischemic stroke, cardiovascular life support, hemorrhage control, intubation, triage, hypothermia, and fibrinolytic use. Of the remaining guidelines, 14 scored between 50% and 60%, and 20 obtained a score of <50%.Conclusion: There are few high-quality, evidence-based guidelines in EMS. Of those that are published, the majority fail to meet established quality measures. Although a lack of randomized controlled trials (RCTs) conducted in the prehospital field continues to limit guideline development, suboptimal methodology is also commonplace within the existing literature.